MANAJEMEN PELAYANAN PUBLIK: PROSEDUR PEMBUATAN SIM DI POLRES CIREBON KOTA - Eka Wildanu; Christianty Christianty (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2018)
Public services carried out by effective governments or corporations can strengthendemocracy and human rights, promote economic prosperity, social cohesion, reducepoverty, improve environmental protection, be wise in the use of natural resources, deepentrust in government and public administration. As a consequence of the implementation ofregional autonomy, the Regional Government is required to improve its performance inorder to provide services to the community. In essence the implementation of regionalautonomy is directed at accelerating the realization of community welfare throughimproving services, empowerment and participation of the community, as well asincreasing regional competitiveness.Keywords: Public Service, Government, Democracy, Resources